AN IMPROVED MEASUREMENT OF B(0)-(B)BAR(0) MIXING IN Z(0) DECAYS - Adeva, B; Adriani, O; Aguilarbenitez, M; Ahlen, S; Akbari, H; Alcaraz, J; Aloisio, A; Alverson, G; Alviggi, M; Ambrosi, G; An, Q; Anderhub, H; et al. (1992)
A more precise determination of the B0-B0 mixing parameter in Z0 decays based on a fourfold increase in statistics has been made using the 1990 and 1991 L3 data. The analysis of the dilepton events, muons and electrons, gives: χB = 0.121 ± 0.017 (stat) ± 0.006 (sys). Using the value of χd measured at the γ(4S) we derive the following limit for χs:χs > 0.16 (90% CL). © 1992.